Analisis Kinerja Keuangan Menggunakan Rasio Profitabilitas Dan Metode Economic Value Added (EVA): (Studi Kasus Pada PT. Bekasi Fajar Industrial Estate Tbk Yang Terdaftar Di BEI Periode 2019-2023) - Dian Anita; Nurdiandani, Nirmala (LPPM POLITEKNIK LP3I BANDUNG, 2024)
This study aims to analyze the financial performance of PT. Bekasi Fajar Industrial Estate Tbk using two main approaches: profitability ratios and the Economic Value Added (EVA) method. This approach is conducted to provide an overview of how effectively the company generates profits and creates value for its shareholders. The study employs a descriptive qualitative method using secondary financial data from the period 2019-2023. The results indicate that PT. Bekasi Fajar Industrial Estate Tbk experienced fluctuations in profitability ratios. A decline was observed in 2020 and 2021 due to the impact of the COVID-19 pandemic, which adversely affected this industrial sector due to the implementation of Community Activity Restrictions (PPKM). Overall, the company's performance in terms of profitability ratios is still below the industry average. The assessment using the EVA method showed fluctuations during the 2019-2023 period but remained positive, indicating that the company is still capable of creating additional value for the shareholders. The implication of this study is the importance of monitoring financial perfomance and adjusting strategies to ensure the company’s sustainability and growth in the future.